Knowledge of Alzheimer’s disease and its relationship with attitude towards genetic testing for the disease: a survey of the general public in Bangladesh - Chowdhury, Sariya Uzrat (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.